Diurnal opposite variation between angiotensinase activities in photo–neuro–endocrine tissues of rats. (21st October 2017) - Domínguez-Vías, Germán; Aretxaga-Maza, Garbiñe; Prieto, Isabel; Luna, Juan de Dios; De Gasparo, Marc; Ramírez-Sánchez, Manuel
ABSTRACT: Central and peripheral renin–angiotensin systems (RASs) act in a coordinated manner for the physiologic functions regulated by neuroendocrine events. However, whereas the diurnal rhythm of peripheral circulatory and tissue RASs is well known, the circadian behaviour of their components in central photo–neuro–endocrine structures, key elements for the control of circadian rhythms, has been barely studied. In the present study, we analysed the aspartyl- (AspAP) and glutamyl-aminopeptidase (GluAP) (aminopeptidase A) activities, the angiotensinases responsible for the metabolism of Ang I to Ang 2–10 and Ang II to Ang III, respectively, in the retina, anterior hypothalamus and pituitary at different light and dark time-points of a 12:12 h light:dark cycle (7–19 h light), using arylamide derivatives as substrates. The results demonstrated that while retina and pituitary exhibited their highest levels of AspAP activity in the light period and the lowest in the dark one, the contrary occurred in the hypothalamus – the lowest levels were observed in light conditions and the highest in darkness. The outcome for GluAP showed the highest levels in the light period and the lowest in the dark one in the three tissues analysed. In conclusion, changes in angiotensinase activities throughout the daytime may cause changes of their respective substrates and derived peptides and, consequently, in their functions. This observation may have implications for the treatment of hypertension.